Female migration: strategies of support and social mobility among Peruvians in Spain and Argentina - Paerregaard, Karsten (2007)
This article studies the gender pattern of Peruvian migration to Spain and Argentina. The author compares the different contexts that migrants face in both countries and the possibilities that are offered to migrant women in terms of jobs and social mobility. The author also analyzes how these opportunities are reflected in the expectations of Peruvian women to support their families in Peru and to be able to bring them to Spain and Argentina in the long run. Additionally, she explores how migrants design strategies to achieve these expectations through a mind-set (imaginario) where migration is represented as a global hierarchical network and migration targets. The questions underlying this research include the following: who are the women that migrate to these two countries? What type of social network do they use to migrate and how do they migrate? Which are the strategies they develop to support themselves and insert themselves in the labor market of Spain and Argentina? Which are the similarities and the differences observed between Peruvian migration to Spain and Argentina, and which are the economic and social opportunities they encounter as migrants? The data on which this paper is based —the migration experiences of three Peruvian women in each country— was gathered through field work which was carried out in Spain, in 1997, and in Argentina, in 2000.